Personalization or Manipulation? Analysis of Personalization Marketing Strategy on Consumer Purchase Decision in Indonesian E-Commerce - Widyatmoko Widyatmoko (North Press, 2025)
This study investigates the impact of personalized marketing strategies (PMS) on consumer purchase decisions in Indonesian e-commerce, using a quantitative analysis with a sample size of 200 respondents. Data was collected through a Likert scale survey (1-5) and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS) 3. The study explores the relationships between personalized marketing strategies, consumer trust, perceived relevance, ethical concerns, and purchase decisions. The results indicate that personalized marketing strategies significantly influence both consumer trust and perceived relevance, which, in turn, positively affect consumer purchase decisions. Ethical concerns were found to have a weaker impact on purchase decisions but still played a role in shaping consumer behavior. These findings offer important insights into the effectiveness of personalized marketing in e-commerce and highlight the need for platforms to focus on trust-building, relevance, and transparency to enhance consumer engagement and drive sales. The study contributes to the understanding of consumer behavior in the context of personalized marketing in emerging markets like Indonesia.